Pengembangan Kawasan Agrowisata Berbasis Komoditas Unggulan di Payo, Solok, Sumatera Barat - Nugrahapsari, Rizka Amalia; Hayati, Nur Qomariah; Ahmadi, Noor Roufiq; Arsanti, Idha Widi; Hardiyanto, Hardiyanto (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 02, Januari 2021, 2021)
Solok City Government has a plan to develop area-based agrotourism in order to develop regional superior commodities. The research objectives are: (1) assessing the existing condition of agriculture and livestock, (2) assessing the role of stakeholder in developing Payo agro-tourism, (3) formulating Payo agro-tourism development strategies. The data used were primary and secondary data. Primary data were obtained from farmer interviews and participatory rural appraisal (PRA), as well as focus group discussions (FGD) with stakeholders. Data were analyzed with interactive analysis techniques and thematic analysis. The results showed that the socio-economic conditions of the community and the commitment of the local government supported the successful development of superior commodities in the Payo agro-tourism area. Potential and superior commodities based on land suitability, community and government interests are coffee, mangosteen, avocado, turmeric, chrysanthemum, and medicinal plants. But still needed support from IAARD technological innovation and institutional arrangement. The recommended steps in the development of Payo agro-tourism in a row are as follows: (1) structuring commodities according to land suitability, (2) providing technical guidance with methods that are easily understood, and (3) providing escort and institutional arrangement in developing agro-tourism areas. The involvement of IAARD in this effort can be started by drafting grand design of IAARD technological innovation support in Payo agro-tourism. Keywords: agro-tourism, area, solok